Market integration and public services in the European Union - Cremona, Marise (Oxford : Oxford University Press, 2011)
Offering an analysis of the most pressing issues relating to the interaction between market integration and the provision of public services in the EU, this book addresses the underlying systemic issues, confronting core tensions at the heart of the EU's social and economic policy.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Trade regulation -- European Union countries; Municipal services -- European Union countries; European Union countries -- Economic integration; European Union countries -- Social conditions